Performance of concrete grout under aggressive chloride environment in Sabah - Imbin, S.; Dullah, S.; Asrah, H.; Kumar, P.S.; Rahman, Muhammad; Mannan, M. (World academy of science, engineering and technology, 2013)
Service life of existing reinforced concrete (RC) structures in coastal towns of Sabah has been affected very much. Concrete crack, spalling of concrete cover and reinforcement rusting of RC buildings are seen even within 5 years of construction in Sabah. Hence, in this study a new mix design of concrete grout was developed using locally available materials and investigated under two curing conditions and workability, compressive strength, Accelerated Mortar Bar Test (AMBT), water absorption, volume of permeable voids (VPV), Sorptivity and 90-days salt ponding test were conducted. The compressive strength of concrete grout at the age 90 days was found to be 44.49 N/mm2 under water curing. It was observed that the percentage of mortar bar length change was below 1% for developed concrete grout. The water absorption of the concrete grout was in between the range of 0.88 % to 3.60 % under two different curing up to the age 90 days. It was also observed that the VPV of concrete was in the range of 0 % to 9.75 and 2.44% to 13.05% under water curing and site curing respectively. It was found that the Sorptivity of the concrete grout under water curing at the age of 28 days is 0.211mm/√min and at the age 90 day are 0.067 mm/√min. The chloride content decreased greatly, 90% after a depth of 15 mm. It was noticed that the site cured samples showed higher chloride contents near surface compared to water cured samples. This investigation suggested that the developed mix design of concrete grout using locally available construction materials can be used for crack repairing of existing RC structures in Sabah.